The relationship between upper extremity pain and ultrasound use in the perinatologist - Yenigül, Ali Erkan; Ercan, Fedi (The European Research Journal, 2022)
Objectives: To examine the relationship between upper extremity problems and the performance of abdominal sonography to provide an understanding of the prevalence of upper extremity pain among perinatologist. Methods: This study was conducted as a prospective trial between June-August 2020. The online questionnaire prepared by the researchers was completed by volunteer perinatologists. It included topics such as age, gender, years of perinatology specialist experience, average number of patients per week, minutes each patient’s examination lasted and other demographic data is performed. Perinatologists with upper extremity pain were assigned to group 1. Group 2 comprised those who had no upper extremity pain. Patients in group 1 were divided into two subgroups according to pain intensity. All data were compared between groups. Results: Overall, 115 perinatologists participated in this research. Of all participants, 82 (71.3%) had upper extremity pain, and 33 (28.7%) had no upper extremity pain. No significant relationship was observed for age, gender, average number of ultrasound examinations per day, or time allotted for each patient’s examination between group 1 and 2. Providers performed perinatology services for 5 years (range: 1-23 years) in subgroup 1A and for 7 years (range: 1-23 years) in subgroup 1B (p = 0.02). Conclusions: Upper extremity pain caused by intensive ultrasound use is common in perinatologists; as the years in the profession increase, the frequency and severity of these pains may increase.